Pengaruh Bauran Pemasaran Terhadap Minat Beli Konsumen Pada Makanan Ringan Usaha Mikro Kecil Dan Menengah (UMKM) - Novi Aisha (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to determine the effect of the marketing mix on consumer buying interest. This study uses a qualitative descriptive approach, which describes the problem studied accurately regarding the facts and causes of the observed phenomena. Data collection techniques used are literature studies, documentation methods, internet searching related to the marketing mix and purchase intention. The results of this study obtained that there was an influence of product, price, place, and promotion on consumer buying interest.